CEACAM2 positively regulates integrin αIIbβ3-mediated platelet functions. (16th November 2016) - Alshahrani, Musaed M.; Kyriacou, Roula P.; O'Malley, Cindy J.; Heinrich, Garrett; Najjar, Sonia M.; Jackson, Denise E.
Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is an Ig-ITIM superfamily member that regulates integrin αIIbβ3 function. We hypothesized that its twin protein, CEACAM2, exerts a similar physiologic role in murine platelets. CEACAM2-deficient mice ( Cc2 −/− ) displayed prolonged tail bleeding times and increased volume of blood loss. Cc2 − / − platelets have moderate integrin αIIbβ3-mediated functional defects with impaired kinetics of platelet spreading on fibrinogen and type I collagen and delayed kinetics in the retraction of fibrin clots in vitro . This functional integrin αIIbβ3 defect could not be attributed to altered integrin αIIbβ3 expression. Cc2 − / − platelets displayed normal 'inside-out' signaling properties as demonstrated by normal agonist-induced binding of soluble fluorescein isothiocyanate (FITC)-fibrinogen and JON/A antibody binding. This data provides direct evidence that disruption of CEACAM2 induces a moderate integrin αIIbβ3-mediated platelet function defect, and that CEACAM2 is essential to maintain a normal integrin αIIbβ3-mediated platelet function.